Application of Big data in football in Indonesia: Systematic Review - Gilang Ramadan; Giofandi Samin (JUARA : Jurnal Olahraga, 2022)
The purpose of this study is to review articles that are carried out systematically and qualitatively synthesized on the application of football sports technology. The research method carried out by conducting a limited search is on research published in the article search period 2017 to 2022 by following prism guidelines, the search is carried out by systematically identifying 155 publications that undergo a review of the title, abstract, or full text. Studies are issued if the article is not in English or does not include the original data. The results of a systematic review found 10 articles that met the eligibility criteria, based on self-reported data that in Indonesia the use of sports technology in football has not been thoroughly used in every aspect of the football organization and there is a need to secure goals related to the use of technology as a whole to advance Indonesian football. The conclusion of this study is that there are still many factors that cause technology and bigdata to be used thoroughly in football.